Stereoselective OsO4-mediated dihydroxylation of β-substituted α-trialkylsilyl-β,γ-unsaturated esters - Anna C. Seal; Michael P. Jennings (Results in Chemistry, 2021)
The dihydroxylation of various of α-trialkylsilyl-β,γ-unsaturated esters with OsO4 and NMO has been explored. It has been revealed that these reactions readily allow for a stereoselective dihydroxylation with high levels of dr (>20/1) to afford anti-aldol products with three contiguous stereogenic centers in modest overall yields.